Tetramethylpyrazine: An Active Ingredient of Chinese Herbal Medicine With Therapeutic Potential in Acute Kidney Injury and Renal Fibrosis - Li, Jun; Gong, Xuezhong (Frontiers in Pharmacology, 2022)
As an increasing public health concern worldwide, acute kidney injury (AKI) is characterized by rapid deterioration of kidney function. Although continuous renal replacement therapy (CRRT) could be used to treat severe AKI, effective drug treatment methods for AKI are largely lacking. Tetramethylpyrazine (TMP) is an active ingredient of Chinese herb Ligusticum wallichii (Chuan Xiong) with antioxidant and anti-inflammatory functions. In recent years, more and more clinical and experimental studies suggest that TMP might effectively prevent AKI. The present article reviews the potential mechanisms of TMP against AKI. Through search and review, a total of 23 studies were finally included. Our results indicate that the undergoing mechanisms of TMP preventing AKI are mainly related to reducing oxidative stress injury, inhibiting inflammation, preventing apoptosis of intrinsic renal cells, and regulating autophagy. Meanwhile, given that AKI and chronic kidney disease (CKD) are very tightly linked by each other, and AKI is also an important inducement of CKD, we thus summarized the potential of TMP impeding the progression of CKD through anti-renal fibrosis.